ESTUDO RETROSPECTIVO DA COBERTURA VACINAL CONTRA FEBRE AFTOSA NO MUNICÍPIO DE CAMPINA GRANDE - PB - Silva, Emanuel Couto da (2017)
Foot-and-mouth disease is an acute infectious disease that has as its main agent a virus and affects production animals worldwide, especially those with split hooves such as cattle, buffaloes, sheep, goats, swine and wild animals. The presence of the disease in the region causes immense economic damages, in animal production as well as sanitary barriers imposed by countries that import in natura products and derivatives. There is no treatment for foot-and-mouth disease, so its control includes preventive-prophylactic measures, such as compulsory vaccination of all bovine and buffalo herds in our country. In Paraiba, the herds are vaccinated every six months, occurring in the months of May and November. Regarding the municipality of Campina Grande - PB, the cattle herd is estimated at approximately 16,000 animals. The data used in this research were obtained through the official agencies involved in PNEFA (National Program for Eradication and Prevention of Foot-and-Mouth Disease). In the study period, the vaccination coverage rates presented considerable oscillations, which may be justified by a failure to execute the program. This study aimed to identify the percentage of vaccination coverage against foot-and-mouth disease in the municipality of Campina Grande between 2012 and 2015.